SCREENING AND PHYTOCHEMICALS TEST OF EXTRACT ENDHOPHYTES BACTERIA FROM STEM OF PACING (Costus sp.) - Aristina, Reza Fauziah; Astuti, Winni; Pratiwi, Djihan Ryn (JURNAL ATOMIK, 2019)
Pacing plants (Costus sp.) Potentially as medicinal plants, but there is no research on the endophytic bacteria they contain. This research was conducted to filter endophytic bacteria from Pacing stems (Costus sp.) And to find out the secondary metabolites contained by each endophytic bacteria. Endophytic bacteria obtained from Pacing Stems (Costus sp.) Totaled 17 colonies. Crude extracts from all bacterial colonies containing alkaloids, 15 crude extracts containing saponins. Steroids are only contained by 3 types of bacterial extracts and triterpenoids are only contained by 2 types of bacterial extract.